PENGARUH PENGGUNAAN METODE PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE (TPS) DAN MOTIVASI BELAJAR SISWA TERHADAP PRESTASI BELAJAR IPS - via, silvia Arianti (Meretas: Jurnal Ilmu Pendidikan; Vol 3 No 3 (2016): Jurnal Ilmu Pendidikan Meretas, 2017)
The SD Negeri 2 Palangka is one of the elementary schools that always exist to try to improve the education quality. The number of groups in the study groups was 12. Based on the background of the study, it is structured research aims: 1). To determine the effect of the learning model Think Pair and Share on the student achievement. 2) To determine the effect of motivation of learning to the student achivement, and 3) To determine the effect of the learning model Think Pair and Share and Motivation Learning simultaneously to the Learning Achievement of fourth Grade Student of SD Negeri 2 Palangka in Academic Year 2014/2015. The design of this research is descriptive quantitative research, where the formulation of problem study and relationships to describe the effect of two independent variables to depe student achievement of the students of IPS at SD Negeri 2 in Academic Year 2014/2015. 2) There is a significant effect of the Motivation Learning to the student achivement of the students of IPS at SD Negeri 2 Palangka in Academic Year 2014/2015. And 3) Stiultaneously, there is a significant effect of the use of the learning model Think, Pair and Share and Motivation Learning to the student achievement of the students of IPS at SD Negeri 2 Palangka in Academic Year 2014/2015. Key words: Think Pair and Share, Learning Motivation, Learning Achievement.